A Case Report of Takayasu’s Arteritis (Ukrainian Journal of Ophthalmology, 2026)
Background: Takayasu’s arteritis is a non-specific autoimmune disease affecting large-size blood vessels, with a predilection for the aorta and its major branches. The most characteristic symptoms include absence or decrease of arterial pulses in the arms and CNS-related abnormalities (arm numbness, pain and paresthesia; fatigue; dizziness; syncope; seizures; aphasia; and hemipareses).Purpose: To exemplify the ocular manifestations of Takayasu disease.Materials and Methods: The patient underwent general clinical tests, comprehensive ophthalmological examination, duplex Doppler sonography of carotid and cerebral vessels, and brain MRI.Results and Conclusion: Our case report demonstrates the severity of the course of the disease and that the prognosis for vision and life in patients with Takayasu's arteritis can be unfavorable. Takayasu's arteritis can be seen in young men, with one of the symptoms being ocular alterations (corneal edema, mydriatic pupil, cataract, changes in retinal vessel caliber, retinal edema and ischemia, and reduced blood flow velocity in the ophthalmic artery).
Keywords: Takayasu’s arteritis; aorto-arteritis